Automatic book binding machine - Adnan, Anis Zafirah (2007)
This thesis describe about the automatic book binding machine. This machine is using the hydraulic system, where the punching process and binding process use hydraulic cylinder. This automatic book binding machine is use a ‘puncher’ concept, and then compiles all the paper to bind. It can operate in two conditions which is manual and automatic. In manual system, it just use direct wiring, while in auto system, it will be controlled by PLC. The programming in PLC are using ladder diagram. In hydraulic system, the motor that will be used is 3 phase motor where is 3hp. The operation start with, the book will be placed in one basement book and the cylinder 1 will retract and punching process will happened. Then the motor will move the basement book to binding stage and the process will continue. To make the operation become smoothly, it used inductive sensor to detect every station to stop. This machine is using less human energy in binding book. The consumer only just push the button to make this machine functioning.